Energy band gap and dispersive optical parameters in Bi1.5Zn0.92Nb1.5O6.92 pyrochlore ceramics - (:unkn) unknown (ELSEVIER SCIENCE SA, 2010)
The compositional and optical properties of Bi1.5Zn0.92Nb1.5O6.92 Pyrochlore ceramics have been investigated by means of scanning electron microscopy (SEM) and UV-vis spectroscopy, respectively. The SEM spectroscopy revealed that the pyrochlore exhibits a very dense microstructure with single-phase appearance. The absorption spectral analysis in the sharp absorption region revealed an indirect forbidden transitions band gap of 3.30 eV. The room temperature refractive index, which was calculated from the reflectance and transmittance data, allowed the identification of the dispersion and oscillator energies, static and lattice dielectric constants and static refractive index as 26.69 and 3.37 eV, 8.92 and 15.95 and 2.98, respectively. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Mixing; Composites; X-ray methods; Optical properties; DIELECTRIC-PROPERTIES; CRYSTAL-CHEMISTRY; THIN-FILMS; SPIN ICE; BI1.5ZNNB1.5O7; TEMPERATURE